Reproductive Pattern, Morphological and Histological Characteristics of Gonads of the Goby Eleotris melanosoma from the Coastline in Soc Trang - Ngan, Le Hoang Truc; Quang, Dinh Minh (VNU Journal of Science: Natural Sciences and Technology, 2017)
This study was conducted in the coastline in Soc Trang to contribute useful information on reproductive pattern, morphological and histological characteristics of ovaries and testes and development of oocytes and spermatocytes per gonadal development stages of the goby Eleotris melanosoma, a commercial fish in the study area. Data analysis of 65 individuals (28 females and 37 males) collected during the wet and dry seasons showed that this species fall into single spawner category since ovaries and testes at the mature and ripe stages comprised stage 4 and 5 of oocytes and spermatocytes. The results not only contributed to reproductive data but also based to set suitable sampling time for sustainable exploitation the fish resources in the study region. This study was conducted in the coastline in Soc Trang to contribute useful information on reproductive pattern, morphological and histological characteristics of ovaries and testes and development of oocytes and spermatocytes per gonadal development stages of the goby Eleotris melanosoma, a commercial fish in the study area. Data analysis of 65 individuals (28 females and 37 males) collected during the wet and dry seasons showed that this species fall into single spawner category since ovaries and testes at the mature and ripe stages comprised stage 4 and 5 of oocytes and spermatocytes. The results not only contributed to reproductive data but also based to set suitable sampling time for sustainable exploitation the fish resources in the study region. Keywords: Eleotris melanosoma, reprodutive pattern, spawning season, Soc Trang.